Detection of cytokines in cervicovaginal lavage in HIV-infected women and its association with high-risk human papillomavirus - Schindler, Sandra; Netto, Eduardo; Deminco, Felice; Figueiredo, Camila A.; de Andrade, Candace Machado; Alves, Amanda Rosa; Brites, Carlos (Frontiers in Immunology, 2024)
Background Women living with HIV/AIDS (WLHA) have an increased prevalence of high-risk HPV infection (HR-HPV) and cervical intraepithelial neoplasia (CIN) and a greater risk of cervical cancer despite access to a new generation of antiretroviral therapy. The aim of this study is to evaluate the concentrations of different cytokines involved in the local immune response in WLHA, which is fundamental for understanding the pathogenesis of HPV-related cancer in this population. Methods IL-1β, IL-2, IL-4, IL-6, IL-10, IFN-γ, TNF-α, IP-10, GM-CSF, and MIP-1α were investigated in the cervicovaginal lavage (CVL) of 106 WLHA attending at Hospital Universitario Professor Edgard Santos in Salvador, Bahia, Brazil, during the period December 2019 to April 2023 by Luminex®. All participants were also tested for Chlamydia trachomatis and Neisseria gonorrhoeae and underwent colposcopy, Pap smear, and Nugent score. HIV plasma viral load (VL) and CD4 cell count were performed for all WLHA. Results In this study, 22.6% (24/106) of WLHA were infected with HR-HPV. A higher proportion of patients with HR-HPV (66.7%) had detectable levels of IL-10 than those negative ones (40.2%, p = 0.02). More premenopausal women had either IL-6 (51.4%) or IP-10 (58.3%) than those in menopausal status (26.5% for IL-6 and 32.4% for IP-10, p = 0.013 and p = 0.011, respectively). Vaginosis was negatively associated with detection of IP-10 (24.2% vs. 61.4%, p < 0.001) and INF-γ (39.4% vs. 68.6%, p = 0.005). A positive association was detected for IL-1β (66.7 vs. 37.1%, p = 0.005) and IL-10 (63.6% vs. 37.1%, p = 0.01). VL and CD4 were not associated with the studied cytokines. Conclusion We demonstrated a positive association between IL-10 and HPV infection in CVL, suggesting the predominance of the Th2 response in HIV/HPV co-infected patients. However, further studies with longer follow-up will be needed to evaluate the association of IL-10 with HPV infection, CIN, and cervical cancer in WLHA.